The Board of Directors and Firm Growth of Small and Medium Enterprises in Malaysia - Yew, Lim Kim; Hoo, Wong Chee; Teck, Tan Seng; Kowang, Tan Owee; Omar, Rosmini; Hee, Ong Choon; Fei, Goh Chin (International Journal of Psychosocial Rehabilitation, 2020)
Prior studies on the role of board of directors and the performance of firm are conducted in large firms. Board of directors’ attributes comprising of board size, board independency and board ownership are used in these previous studies. In addition, accounting ratio such as return on asset and return on equity are employed in these previous studies as the performance indicator. Nevertheless, the study on the role of board of directors and firm performance using growth as an indicator in Small Medium Enterprises (SMEs) has yet to take its ground. Thus, this present study aims to assess the role of the board of directors and firm growth in Malaysia SMEs’ context. This present study has examined the roles of board of directors, namely, board transparency, board guanxi and board entrepreneurial orientation in relation with SMEs’ firm growth as a performance indicator. The objectives of this study are to predict overall SMEs’ firm growth based on the roles of the board of directors. Survey questionnaire was used to collect data from a total of 205 respondents. The empirical results revealed that board transparency, board guanxi and board entrepreneurial orientation are positively and significantly associated with SMEs’ firm growth.